Wearable Doppler Radar with Integrated Antenna for Patient Vital Sign Monitoring. Issue 4 (19th May 2017) - Ebrahimian, Homayoun
ABSTRACT: In this article, a wearable Doppler radar unit with radio data link in 2.4 GHz for use in portable patient monitoring and emergency response is presented. By using a rotated E-shaped strip in the radiating patch, a new resonance at lower frequencies (2.4 GHz) can be achieved. Also, by embedding cutting a rectangular slot with protruded interdigital strip inside the slot in the feed line a frequency band-stop performance can be achieved. The proposed structure has a major advantage in high harmonic rejection. In order to generate efficient RF to dc conversion, we use a pair of gap distances in the microstrip loop. Unlike portable electrocardiograms (ECG) or photoplethysmography, the near-field Doppler unit enables monitoring of the person's heart rate without the need for electrical contact or optical access to the patient's skin. The Doppler unit is designed to be embedded in a clothing garment, such as a shirt or vest, or used by medical emergency personnel in an instrumented blanket or medical stretcher. Since the Doppler unit is placed directly on or behind the patient's torso, the extraneous signals due to relative motion artifacts are greatly reduced. Low-cost design is achieved by employing pulse wideband microstrip elements for the integrated patch antenna, microwave oscillator, and tuning elements. Also, since the distance between the Doppler unit and the patient is fixed, it was possible to tune the detection phase to enable the use of a single mixer diode and eliminate the need for quadrature detection. This approach is demonstrated using a simple direct conversion radar circuit implemented in a microstrip operating at 2.460 GHz. Heart rate data is shown for detection distances of 0.5 meter. Measured heart data from this technique shows a clear waveform substructure similar to the Personal Questionnaire Rapid Scaling Technique complex features found in captured ECG data.